Performance ranking of Turkish insurance Companies: THE anp application - (:unkn) unknown (My University, 2014)
Karar verme kavramı, eğer sonuçlar kesin değilse opsiyonlardan bir tanesinin seçimi süreci olarak tanımlanabilir. Karar vermenin en basit şekli olan bir kritere dayalı olarak karar verme pratikte opsiyonların değerlendirilmesi için yeterli değildir. Böyle hallerde en iyi opsiyonu seçmek için farklı bilgilerin tamamını gözönüne almalıyız ki bu durum çok kriterli karar verme metotlarının gerekliliğini ortaya çıkarmıştır. AHP (Analitik Hiyerarşi Süreci) farklı mertebeden ilişkileri modelleyen bir tekniktir. Diğer tarafan bu teknik karşılıklı ilişkilerin değerlendirilmesinde yetersiz kalmaktadır. ANP(Analitik Ağ Süreci) konu ile ilgili bütün kriterlerin kullanılmasına olanak sağlar. ANPnin ilk aşaması bütün sistemdeki kriterleri karşılaştıran süper matrisi oluşturmaktır ki burada ikili karşılaştırmalar uzmanlara sorularak oluşturulur. ANPnin ilk adımı her bir kriter arasındaki önemin karşılaştırılmasıdır. Sonraki adımı özdeğer metodunu kullanarak her bileşendeki kriterlerin etkisinin hesaplanmasıdır. Bu çalışmada, süper karar yazılımı ile ANP modeli uygulanarak 2006 - 2010 yılları arasında Türk sigorta sektöründe hayat dışı branşında faaliyet gösteren büyük ölçekli şirketlerin fnansal fnansal performans sıralaması yapılmıştır.

Decision making concept can be defned as selection process choosing one of the options, if the outcomes are not certain. In practice it is not sufcient to evaluate the options according to the simplest form of decision making only based on a criterion. In such cases, we must consider all the variety of diferent information to decide to best option. It arise the requirement of multi-criteria decision making methods. AHP (Analytical Hierarch Process) is a technique that models the relations which are diferent stage. On the other hand that technique is insufcient to evaluate interdependency relations. Te ANP (Analytic Network Process) has the ability to add all the criteria related with the issue. Te method of the ANP can be described as follows. Te ﬁrst phase of the ANP is to compare the criteria in whole system to form the supermatrix. Tis is done through pairwise comparisons by asking experts. Te ﬁrst step of the ANP is to compare the importance between each criterion. Te next step is to calculate the inﬂuence of the elements (criteria) in each component (matrix) using the eigenvalue method. In this research, fnancial performans ranking of Turkish Insurance companies, which large-scaled business in non-life branches, are obtained for the period 2006-2010 using fnancial ratios of companies and applying the ANP model which was developed with the superdecision sofware.
Türk sigorta şirketlerinin performans sıralaması: Anp uygulaması
Keywords: İktisat; İşletme